Morphometric Indices and Venom Protein Profile in Different Populations of Androctonus crassicauda - Mohammad Bagher Ghavami; Zohreh Alibabaei; Fatemeh Ghavami (Tehran University of Medical Sciences, 2022)
Background: Androctonus crassicauda is the most medically relevant animal and understanding its morphological characteristics is essential in the production of antiscorpion sera. Methods: Adults of A. crassicauda were collected from different areas of Zanjan Province and the morphometric parameters and the cuticular fluorescence patterns of samples were studied. The crude venom of samples was extracted by electric stimulation, and their biochemical properties were analyzed by the SDS-PAGE method. Results: Values of the morphometric parameters depended on sex and altitude of the area. Except for values of the pectinal organ, these parameters in females were higher than in males. No significant difference was in the number, shape, and intensity of cuticular fluorescence patterns. The body length of males in high and lowlands was 72.53±1.53 and 77.33±2.70mm, respectively. Females' body lengths in that area were 81.66±2.19 and 86.55±2.33mm, respectively. Analysis of toxin proteins showed two isotypes that the 12, 13, 15, 16, 18, and 19kDa proteins were in all areas. However, the 41 and 74kDa proteins, and 46 and 63kDa proteins were detected in low and highlands, respectively. Conclusion: Black fat-tailed scorpion has a considerable dominancy and developing preventive programs and providing treatment facilities in studied areas are necessary. Values of the morphological parameters and venom electrophoresis patterns depended on the geographical location. Therefore, pool crude toxin is suggested for the production of effective antivenoms. Moreover, additional field complementary works in the geographic information system based niche modeling and mass fingerprinting of scorpion venoms are suggested for screening effective isotypes.